K+ , Na+ , Mg2+ , Ca2+ , and water contents in human skeletal muscle: correlations among these monovalent and divalent cations and their alterations in K+ -depleted subjects - Tavichakorntrakool, Ratree; Prasongwattana, Vitoon; Sriboonlue, Pote; Puapairoj, Anucha; Wongkham, Chaisiri; Wiangsimma, Thitichai; Khunkitti, Wattana; Triamjangarun, Sombat; Tanratanauijit, Maneewan; Chamsuwan, Amporn; Khunkitti, Wirut; Yenchitsomanus, Pa-Thai; et al. (Translational research : the journal of laboratory and clinical medicine, 2007)
None of previous studies had simultaneously analyzed the K+ , Na+ , Mg2+ , and Ca2+ contents in human skeletal muscle. We examined extensively and simultaneously the levels of all these cations and examined water content in vastus lateralis and pectoralis major muscles in 30 northeastern Thai men who were apparently healthy but died from an accident. Specimen collection was performed within 6 h of death. We used atomic absorption or flame photometry to measure the level of muscle cation. Histopathology of muscle and kidney was also evaluated. K+ , Na+ , Mg2+ , and Ca2+ contents in vastus lateralis were 84.74 ± 1.50, 38.64 ± 0.77, 7.58 ± 0.17, and 0.94 ± 0.06 μmol/g wet weight, respectively, whereas K+ , Na+ , and Mg2+ contents in pectoralis major were 82.83 ± 1.54, 37.57 ± 0.72, and 7.30 ± 0.17 μmol/g wet weight, respectively. The water component was comparable in vastus lateralis and pectoralis major (78.66 ± 0.41 and 78.09 ± 0.56 %, respectively). Based on muscle K+ levels, we divided the subjects into 2 main groups: K+ -depleted (KD) group (K+ < 80 μmol/g wet weight; n = 7) and non–K+ -depleted (NKD) group (K+ >= 80 μmol/g wet weight; n = 23). In the KD muscle, Na+ and Ca2+ levels were significantly higher, whereas the level of Mg2+ was significantly lower. Linear regression analysis showed significant correlations of K+ and Mg2+ levels and between Na+ and Ca2+ . However, K+ and Mg2+ had the negative correlation with Na+ and Ca2+ . Histopathologic examination showed no change in the KD muscles, whereas 29% (2 of 7) of the KD kidneys had vacuolization in proximal renal tubular cells. Our study not only provided the descriptive data but also implied the balance or homeostasis of these monovalent and divalent cations in their muscle pools.